Classroom Interaction Analysis on Kindergarten School - Cahyani, Mia; Supriyono, Yusup; Tandiana, Soni Tantan (Jurnal Metaedukasi: Jurnal Ilmiah Pendidikan, 2025)
Classroom interaction is an essential part of the teaching and learning process in the classroom. This study aims to understand the interactions that occur between teachers and students in a kindergarten setting. The study involved one teacher and 20 students. This research used a qualitative method, namely a descriptive case study. Data were collected through video-recorded observations. The data were analyzed using the theory of Miles and Huberman (1994). The study shows that teacher-student interactions can be seen from teacher talk and student talk. In teacher talk, several indicators emerged, such as: dealing with feelings, praising and encouraging, using the ideas of students, asking questions, giving information, and giving direction. Meanwhile, in student talk, there are indicators like student response, specific, nonverbal, silence, student-initiated, and laughter. Asking questions is the most frequently used by the teacher, while student response, specifically, is the most dominant response by the students.